Mobilised emotions: public transportation in the Jim Crow era, 1896-1964 - Pearce, Rosemary (2018)
This project works to unveil emotional experiences on segregated public transportation from 1896 to 1964. In so doing, it opens up how feelings evoked by racial conflict on public transportation helped to fuel the black rights movement that demanded the end of the segregated system. Through examining plaintiffs of civil rights test cases, Pullman porters, members of the armed forces in the Second World War, and grassroots activists of the 1950s and 1960s, the thesis reassesses the familiar topics of segregated transportation and black resistance to it through the lens of emotions. It shows not only that the feelings of African Americans were systematically dismissed, ignored, and suppressed, but also that the expression of certain emotions was mandatory for black passengers. Deviating from these emotional norms often resulted in verbal or physical abuse, hindering the protest of discriminatory treatment perpetrated by white police, bus drivers, conductors, and passengers. Finally, the thesis uncovers how black activists responded to this everyday form of racial control by converting emotional self-regulation into a weapon with which to attack segregation. The emotional context of segregated public transportation in this period has hitherto been neglected, but following the emotional turn in history, this project works to illuminate the full extent of the racial control white Americans exerted over the expression of African American emotion. Recognising this distinct form of oppression has implications for the study of the Jim Crow era more widely, and in particular the long civil rights movement.